Improvement of the fluorescent sensing biomarker 3-nitrotyrosine for a new luminescent coordination polymer by size regulation. Issue 47 (15th November 2022) - Geng, Jun; Lin, Hongyan; Li, Xiaohui; Lu, Junjun; Wang, XiuLi
Abstract : A new 3D luminescent coordination polymer (LCP) 1 was synthesized for detecting biomarker 3-nitrotyrosine. By adjusting the reaction conditions, Nano-LCP 1 was synthesized, which has a more lower detection limit compared with LCP 1 . Abstract : Luminescence sensing of biomarker 3-nitrotyrosine (3-NT) with coordination polymers (CPs) is of great significance and rarely investigated, especially in improving the sensing performance by regulating the particle of CPs. Herein, we synthesized a new 3D LCP, [Cd3 (L)(BTC)2 (H2 O)2 ]·2H2 O (LCP 1 ) (H3 BTC = 1, 3, 5-benzenetricarboxylic acid, L = ( E )-4, 4′-(ethene-1, 2-diyl)bis[( N -pyridin-3-yl)benzamide]), which demonstrates a rare example of direct detecting 3-NT by LCPs as fluorescent sensors. Meanwhile, nanoscale LCP 1 (Nano-LCP 1 ) with a smaller size was prepared by adjusting the reaction conditions. Nano-LCP 1 not only shows the same high selectivity, anti-interference ability and fast response time as LCP 1, but also has a higher quantum yield (31.80%, about 3 times that of Bulk-LCP 1 ) and a lower detection limit (2.30 × 10 −8 M, about 20 times that of Bulk-LCP 1 ). A detailed detection mechanism of LCP 1 towards 3-NT and the effect of the size difference on the luminescence sensing performance were discussed, providing a valuable reference for the rational design, mechanism interpretation, and performance improvement of LCP-based fluorescence sensors.